Limits of restrictions of human rights and freedoms to ensure security (problem statement - A. E. Evstratov; I. Yu. Guchenkov (Правоприменение)
The subject. The world faced a coronavirus pandemic in 2020. Many states, including Russia, adopted harsh measures that were largely based on restricting human rights and freedoms in an effort to counter pandemic spread. Inter-State borders were closed, restrictions were imposed on the operation of public catering organizations and the holding of sports and entertainment events was suspended, some of the fundamental rights were heavily con-strained. This resulted in the growth of public disaffection, falling of incomes and a worsening of the overall economic environment. As a result, the problem of the permissibility of restrictions of human rights and freedoms for the sake of public security, as well as the requirements for such restrictions, had once again become relevant.The purpose of the article is, firstly, to learn what is the concept of “freedom” nowadays, to define the conditions and principles of application the permissible restrictions on human rights and freedoms, their aims and purpose. The authors dare to analyze the laws and regulations establishing the possibility of restricting human rights and freedoms and to give a description of the procedure for imposing restrictions in situations of greater danger.The methodology of research includes formal legal interpretation of legal acts, systemic approach to cognition of social relations, analysis and synthesis.The main results, scope of application. The definition and concept of freedom, its limited character, the regulation of the possibility of its restriction for the purpose of protecting society have been studied and defined. Russian and international legislation on the restriction of human rights and freedoms has been analyzed. The principles on the basis of which it is permissible to restrict human rights and freedoms have been identified. The principle of the inadmissibility of restrictions on all rights and freedoms; the adequacy of the imposed restrictive measures to the existing threat; the principle of economic efficiency; the principle of detailed regulation of the imposed restrictions are among them. It has been found out that there is a threat of establishing tyranny with arbitrary restrictions on human rights and freedoms.Conclusions. In today’s world, the restriction of human rights and freedoms should be considered as a necessary measure to ensure the security of the individuals and of society as a whole, especially in the situations of a great danger to public interests. At the same time, the imposing restrictions should be strictly regulated and, moreover, possible abuses should be avoided in order to minimize the negative consequences and avoid establishing totalitarian regime.